2008
DOI: 10.1002/ijc.23459
|View full text |Cite
|
Sign up to set email alerts
|

Selected class I and class II HLA alleles and haplotypes and risk of high‐grade cervical intraepithelial neoplasia

Abstract: Human leukocyte antigens (HLAs) present foreign antigens to the immune system and may be important determinants of cervical neoplasia. Previously published associations between HLA and cervical neoplasia exhibit considerable variation in findings. The biomarkers of cervical cancer risk (BCCR) case-control study addressed the role of specific HLA alleles as cofactors in the development of high-grade cervical intraepithelial neoplasia (HG-CIN) based on the most consistent evidence from published literature. Case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
5
15
2
Order By: Relevance
“…These results are in concordance with cervical cancer studies on Swedish women [23,27], southwestern Hispanic women from the United States [28], Norwegian women [29] and northeastern Brazilian women [30]. Conversely, a significant protective association for the DRB1*15-DQB1*06 haplotype was observed in U.S. and Chinese populations with respect to cervical precancer [31,32] and cancer cases [33], respectively. Other reports indicated no association for the DRB1*15-DQB1*06 haplotype with respect to cervical cancer/precancer [34,35].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in concordance with cervical cancer studies on Swedish women [23,27], southwestern Hispanic women from the United States [28], Norwegian women [29] and northeastern Brazilian women [30]. Conversely, a significant protective association for the DRB1*15-DQB1*06 haplotype was observed in U.S. and Chinese populations with respect to cervical precancer [31,32] and cancer cases [33], respectively. Other reports indicated no association for the DRB1*15-DQB1*06 haplotype with respect to cervical cancer/precancer [34,35].…”
Section: Discussionsupporting
confidence: 93%
“…No association was established for the DQB1*03 allele, either with cervical precancer/cancer or with HPV infection, consistent with prior studies in a Canadian population [32], ethnically admixed Costa Rican women [36], Norwegian women [29], northeastern Brazilian women [30], Senegalese women [51], and Swedish women [27]. However, various studies have indicated an association of the DQB1*03 allele with the risk of development of cervical cancer [23,28,29,34,37,40,47,52].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Whether the amount of sHLA-G production and magnitude of HLA-G membrane expression or the balance between HLA molecules on the cervical cell surface that produce inhibitory or stimulatory signals for NK cells is necessary to modulate the outcome of the infection are questions that need to be further explored. Although other HLA class I and class II classical genes have been associated with SIL, [44][45][46][47] the results of the present study indicate that HLA-G polymorphisms as well as the HPV type are associated with SIL. To clarify the function of HLA-G alleles in SIL susceptibility, it would be interesting to conduct a longitudinal study on normal women exhibiting HPV infection with no SIL to determine whether these alleles are associated with elimination or persistence of HPV infection.…”
Section: Hla-g In Patients Stratified According To Lesion Severity Ancontrasting
confidence: 50%
“…The specifics of this study have been described in detail elsewhere. 13 The authors have analyzed 539 cases with histologically confirmed disease and 833 controls recruited between January 2001 and April 2009. The ethics review boards of the authors' institutions approved the protocol and consent procedures, and all subjects provided written informed consent.…”
Section: The Biomarkers Of Cervical Cancer Risk Studymentioning
confidence: 99%